SAT0572 Liver Fat Indices Relate with Inflammatory Profile in Inflammatory Arthritis Patients. (15th July 2016) - Bruno, C.; Tripolino, C.; Ursini, F.; Nicolosi, K.; Naty, S.; Grembiale, R.D.
Abstract : Background: Rheumatic diseases associate with metabolic and cardiovascular disorders [1]. These complications might be a side effect of drugs exposure (i.e. corticosteroids) but also a direct consequence of the widespread systemic inflammation. While the association between inflammatory markers and metabolic disturbance has been extensively explored, few data are available about liver involvement in inflammatory arthritis [2]. Objectives: To explore possible association between inflammatory markers and serum indicators of non-alcoholic fatty liver disease (NAFLD) in a sample of unselected inflammatory arthritis subjects. The liver fat score (LFS) and the hepatic steatosis index (HSI) were employed as serum NAFLD markers [3]. Methods: Subjects who met ACR/EULAR criteria for rheumatoid arthiritis (RA), CASPAR criteria for psoriatic arthritis (PsA) and ESSG criteria for undifferentiated spondiloarthritis (uSPA) were consecutively recruited for the present investigation. After overnight fasting, the following serum analytes were determined: blood glucose, lipids, insulin, complete blood count, erythrocyte sedimentation rate (ESR), high sensitivity C-Reactive Protein (hsCRP). LFS was calculated with the formula: -2.79 + 1.18 * Metabolic Syndrome (yes=1/no=0) + 0.45 * Type 2 Diabetes (yes=2/no=0) + 0.15 * Insulin + 0.04 * AST - 0.94 * AST/ALT. HIS was calculated with the formula: 8 * ALT/AST + BMI +2, if DM2; +2, if females. Metabolic syndrome was defined according to the criteria of the International Diabetes Federation. Pearson's or Spearman's correlation analyses were used as appropriate to test the associations between continuous variables. Not normally distributed variables were log-transformed before analysis. Results: Overall, a total of 55 subjects (27 AR, 18 PsA and 10 uSPA) were recruited. The prevalence of female gender was 60%. The mean age was 53.5±9.8. Twenty-four patients were under stable treatment with methotrexate (MTX). In simple correlation analyses, LFS significantly correlated with ESR (r=0.37, p<0.01), LnCRP (r=0.46, p<0.001), complement C3 (r=0.46, p<0.001), BMI (r=0.55, p<0.001), Waist (r=0.52, p<0.001); HSI significantly correlated with ESR (r=0.40, p<0.01), LnCRP (r=0.28, p=0.05), complement C3 (r=0.38, p<0.01). After correction for MTX therapy, waist and BMI only ESR and complement C3 correlated with LFS and HSI. Conclusions: The results of the present study, although conducted in a limited sample, demonstrated an interesting association between liver fat indices and inflammatory markers. Our data, if confirmed in other population, might add important information about the relationship linking metabolic complications and rheumatic diseases. References: Avina-Zubieta JA, Thomas J, Sadatsafavi M, et al. Risk of incident cardiovascular events in patients with rheumatoid arthritis: a metaanalysis of observational studies. Ann Rheum Dis. 2012;71:1524–1529. Selmi C, De Santis M, Gershwin ME. Liver involvement in subjects with rheumatic disease. Arthritis Res Ther. 2011;13:226. Kahl S, Straßburger K, Nowotny B, et al. Comparison of liver fat indices for the diagnosis of hepatic steatosis and insulin resistance. PLoS One. 2014;9:e94059. Disclosure of Interest: None declared